Biocompatibility and antibacterial properties of pure titanium surfaces coated with yttrium-doped hydroxyapatite. (December 2019) - Zhang, Kailiang; Zhang, Baoping; Huang, Chunjuan; Gao, Shuting; Li, Bo; Cao, Rui; Cheng, Jingyang; Li, Ruiping; Yu, Zhanhai; Xie, Xiaodong
Abstract: The repair and regeneration of peri-implant soft tissues is essential for the long-term clinical successes of implants. Surface modification of implants using coatings is an effective approach to improving their biocompatibility and antibacterial properties. In this study, we introduced a novel implant material by modifying the surface of pure titanium (Ti). Hydroxyapatite (HA) and HA doped with different concentrations of yttrium (Y) via layer by layer self-assembly method (LBL). Surface morphology, roughness, element composition, and hydrophilicity indicated that the coatings could improve the biological activity without significantly increasing surface roughness. We also examined its biocompatibility with human gingival fibroblasts (HGFs) (proliferation, adhesion, morphology, spreading, and Type I collagen (Col-1) synthesis) and antibacterial properties against Streptococcus mutans . The modified coatings significantly enhanced the proliferative, adhesive, and spreading capacities of HGFs compared to the pure Ti substrate. Col-1 secretion by HGFs positively increased with increased Y doping and duration of cell cultivation, suggesting that the coatings may promote connective tissue formation. Furthermore, increased Y doping significantly reduced the number of adherent S. mutans . Thus, Y-doped HA coatings improve biocompatibility and antibacterial properties, suggesting they have high potential for improving the repair, regeneration, and integration of soft tissues on the surfaces of Ti implants. Graphical abstract: Image 1 Highlights: Yttrium (Y)-doped HA and hydroxyapatite (HA) were successfully coated on Titanium (Ti) implants. Yttrium (Y)-doped HA coating exerts superior biocompatibility and antibacterial properties compared with pure HA coating. Yttrium (Y)-doped HA coatings improve soft tissue repair, regeneration on Ti implant surface.